2020
DOI: 10.1159/000506293
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Index as Prognostic Indicator in Patients Receiving Lenvatinib Treatment for Unresectable Hepatocellular Carcinoma

Abstract: Background/Aim: Few studies have examined the details of nutritional status in patients with unresectable hepatocellular carcinoma (u-HCC) undergoing systemic chemotherapy with lenvatinib. We evaluated the prognostic/predictive value of nutritional status using Onodera's prognostic nutri-tional index (O-PNI) for overall survival among patients with u-HCC treated with lenvatinib. Methods: Three-hundred and seventy-five u-HCC patients treated with lenvatinib were enrolled (median age 72 years; Child-Pugh class A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
(40 reference statements)
2
29
2
Order By: Relevance
“…These reports indicate that BTR is not only a crucial nutritional indicator, but also a prognostic factor for patients with HCC. Similar to our findings, Hiraoka et al 17 recently reported the importance of pre‐treatment nutritional status in lenvatinib treatment using Onodera's prognostic nutritional index. As shown in AE profile (Table 2), treatment with lenvatinib was associated with a higher risk for worsening of nutritional status, which could lead to the dose reduction or treatment discontinuation.…”
Section: Discussionsupporting
confidence: 92%
“…These reports indicate that BTR is not only a crucial nutritional indicator, but also a prognostic factor for patients with HCC. Similar to our findings, Hiraoka et al 17 recently reported the importance of pre‐treatment nutritional status in lenvatinib treatment using Onodera's prognostic nutritional index. As shown in AE profile (Table 2), treatment with lenvatinib was associated with a higher risk for worsening of nutritional status, which could lead to the dose reduction or treatment discontinuation.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported that the PNI is a prognostic factor in HCC patients receiving surgical treatment [97,98] or sorafenib treatment [99,100]. The PNI was strongly correlated with the ALBI score and the predictive cut-off values of the PNI for ALBI grade 1 and mALBI grade 2a were 39.0 and 36.0, respectively [101]. Based on these studies, the nutrition status is considered to impact the prognosis in advanced HCC patients who are treated with lenvatinib.…”
Section: Nutrition Assessment As a Prognostic Indicatormentioning
confidence: 99%
“…On the other hand, only a few studies explored possible prognostic factors in patients treated with lenvatinib. [13][14][15] To fill this gap, the aim of the present study was to evaluate a new prognostic index through a statistical method for analysis of multiple variables, named recursive partitioning analysis (RPA), that creates a regression-treebased on prognostic value. 16…”
Section: Introductionmentioning
confidence: 99%